Group four permethylindenyl-phenoxy (PHENI*) complexes for the synthesis of polyolefins - Collins Rice, CG (2023)
This thesis discusses the synthesis and characterisation of ansa bridged permethylindenyl phenoxy (PHENI*) complexes and their applications in the synthesis of polyolefins. Efficient homogeneous and slurry phase catalyst systems are developed for the homopolymerisation of ethylene and propylene, and a range of copolymerisations incorporating linear α olefins.